Creating Anna Karenina - Blaisdell, Bob (Pegasus Books, 2020)
Intro – Title Page – Dedication – Foreword – A Note on the Spellings of Russian Names – Introduction – Chapter 1: Readying for
Description based on publisher supplied metadata and other sources
Keywords: Tolstoy; Leo; Karenina; Anna; Karenina; Anna - (Fictitious character); Anna Karenina; Aristocracy (Social class); Man-woman relationships; Married women; Adultery; Wives; Electronic books; Karénine; Anna (Personnage fictif); Relations entre hommes et femmes; Femmes mariées; wives; Manners and customs; collective biographies; Biographies